2014
DOI: 10.1111/pace.12518
|View full text |Cite
|
Sign up to set email alerts
|

Increased Long‐Term Mortality in Patients with Cardiovascular Implantable Electronic Device Infections

Abstract: CIED recipients who develop device infection have increased, device-dependent, long-term mortality even after successful treatment of infection. The etiology of this persistent increased risk of death associated with CIED infection is unknown and merits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 15 publications
2
40
0
Order By: Relevance
“…This response is also not unexpected, as postoperative CIED infection caries an alarmingly high morbidity and mortality approaching 5% with long-term effects that can last up to 3 years, dependent on the type of device. [12][13][14][15][16] In this study, of the 10 patients (0.8%) who developed a definite infection after CIED implant (within 60 days), only one had a preoperative WBC count which was elevated (11.7 × 10 3 /uL) and in fact the highest WBC count (29 × 10 3 /uL) was noted in a patient without infection. The overall preoperative WBC count between the two groups (those with and without infection) was not found to be of statistical significance.…”
Section: Although Not Specifically Indicated Preoperative Laboratorymentioning
confidence: 55%
See 1 more Smart Citation
“…This response is also not unexpected, as postoperative CIED infection caries an alarmingly high morbidity and mortality approaching 5% with long-term effects that can last up to 3 years, dependent on the type of device. [12][13][14][15][16] In this study, of the 10 patients (0.8%) who developed a definite infection after CIED implant (within 60 days), only one had a preoperative WBC count which was elevated (11.7 × 10 3 /uL) and in fact the highest WBC count (29 × 10 3 /uL) was noted in a patient without infection. The overall preoperative WBC count between the two groups (those with and without infection) was not found to be of statistical significance.…”
Section: Although Not Specifically Indicated Preoperative Laboratorymentioning
confidence: 55%
“…Despite this, however, the well‐established notion of leukocytosis as a representation of infection leads to trepidation on part of the implanting physician. This response is also not unexpected, as postoperative CIED infection caries an alarmingly high morbidity and mortality approaching 5% with long‐term effects that can last up to 3 years, dependent on the type of device …”
Section: Discussionmentioning
confidence: 99%
“…Device infection is associated with increased mortality in patients receiving CIED therapy . Some investigators have reported that CIED recipients who develop device infection have increased, device‐dependent, long‐term mortality even after successful treatment of infection .…”
Section: Managing Cied Infectionmentioning
confidence: 99%
“…Thus, in the past, not infrequently, leads or remaining lead fragments were left behind after HTX. Prior studies have shown that immunosuppressive therapy represents a significant risk factor for pacemaker infections, and thus remaining lead fragments pose a high risk for potentially life‐threatening complications after transplantation 6,7 . After a transplant, patients require a lifetime, precisely tuned, immunosuppressive therapy, which needs constant medical attention to minimize the risk of rejection.…”
Section: Introductionmentioning
confidence: 99%